Dynamic Splitting Tensile Properties and Failure Mechanism of Layered Slate. (17th August 2020) - Liu, Yunsi; He, Chushao; Wang, Shiming; Peng, Yaxiong; Lei, Yong
Abstract : Dynamic tensile failure is one of the main failure modes of layered rock masses during the excavation of underground engineering. This study investigates the influence of loading rate and layered inclination angle on the mechanical properties and failure mechanisms of layered slate using a split-Hopkinson pressure bar system and high-speed cameras. The results show that, overall, the dynamic elastic modulus E, postpeak stress reduction rate K, and failure load of the discs with the 7 tested bedding angles increase with the increasing loading rate. A nonlinear formula is proposed to describe the relationship between loading rate and failure load for the 7 tested inclination angles. As the inclination angle of the bedding planes increases from 0° to 90°, both the static and dynamic failure loads of the slate increased. However, with increasing loading rate, the anisotropic influence coefficient N ranges from 3.25 under the static load to 1.35 under the dynamic load, and the bedding effect gradually decreases. From the dynamic Brazilian splitting tests, the failure of the discs is mainly observed along the bedding planes when the inclination angle is less than or equal to 45°. Failure of the discs mainly occurs along the centre of the disc and previously intact planes when the inclination angle is greater than 60°. This study provides significant data to evaluate the mechanical properties and failure mechanisms of layered rock and the safety and stability of layered rock under dynamic loading.